Vitamin D as a Potential Agent for Ischemic Axonal Regeneration after Epineurial Devascularization of the Sciatic Nerve - Erdem, Huseyin; Sarikcioglu, Levent; Boyan, Neslihan; Oguz, Ozkan (Current Neurovascular Research, 2019)
Background: Although vitamin D has several noncalcemic functions particularly on nervous system, its neuroregenerative roles on ischemic peripheral nerve injury has not been reported. In this study, it was aimed to investigate the effect of vitamin D3 after epineurial devascularization of the sciatic nerve. Methods: Forty adult female Wistar rats were randomly divided into four groups: Group 1 (Control), Group 2 (Sham-operated), Group 3 (Epineurial devascularization + vitamin D3 treatment), Group 4 (Epineurial devascularization + vehicle treatment). Recovery of the sciatic nerve was analyzed by functional (sciatic functional index, pinch test and biochemical analyses) and morphological (electron microscopic analysis and wet muscle weight analysis) methods. Results: Comparison of the data revealed that vitamin D3 administration had a beneficial effect on regeneration after epineurial devascularization. Conclusion: We suggest that vitamin D3 is an effective agent in the prevention of ischemic peripheral nerve insults.
Keywords: vasa nervorum